Violin jazz in autumn 9 pieces for violin and piano - Iles, Nikki 1963- (Oxford University Press, 2016)
"With fully notated rhythms, grooves, and improvisations, Violin Jass in Autumn is the perfect collection for instrumentalists looking for that authentic sound."--Back cover.